Comparative Study on the Efficacy of Gingival Retraction using Polyvinyl Acetate Strips and Conventional Retraction Cord – An in Vivo Study - M. Shivasakthy; Syed Asharaf Ali (Journal of Clinical and Diagnostic Research, 2013)
Statement of Problem: A new material is proposed in dentistry in the form of strips for producing gingival retraction. The clinical efficacy of the material remains untested. Purpose of the Study: This study aimed to determine whether the polyvinyl acetate strips are able to effectively displace the gingival tissues in comparison with the conventional retraction cord. Material and Methods: Complete metal ceramic preparation with supra-gingival margin was performed in fourteen maxillary incisors and gingival retraction was done using Merocel strips and conventional retraction cords alternatively in 2 weeks time interval. The amount of displacement was compared using a digital vernier caliper of 0.01mm accuracy. Results were analyzed statistically using Paired students t-test. Results: The statistical analysis of the data revealed that both the conventional retraction cord and the Merocel strip produce significant retraction. Among both the materials, Merocel proved to be significantly more effective. Conclusion: Merocel strip produces more gingival displacement than the conventional retraction cord.